Modified cardiological physiotherapy model - Bogacz, Katarzyna A.; Śliwiński, Zbigniew; Dybek, Tomasz; Krajczy, Marcin; Łuniewski, Jacek; Matelonek, Dagmara; Szczegielniak, Jan (Medical Studies/Studia Medyczne, 2016)
According to the World health Organization (WHO), “physiotherapy is a comprehensive and coordinated use of medical, social, professional supplies and educational measures in order to adapt patients to new lifestyle and allow them to get better physical fitness.” In the case of patients who suffer from cardiovascular diseases it refers to complex cardiological rehabilitation (CRR). Constant elements of CRR: review of clinical status of patient, optimization of pharmacological treatment, rehabilitation — gradual and controlled exercises adapted to individual possibilities. At the time of CRR implementation, the period of early rehabilitation (stages I, II) and the period of late rehabilitation (stage III) are distinguished.